Effect of suspended particles on convective heat transfer enhancement. - Aydin, M. (2012)
In this paper we numerically study the inﬂuence of particles suspended in ﬂows on heat transfer enhancement. We consider two ﬂat horizontal parallel plates kept at the same temperature, where hot air with particles ﬂows in between. High-conductive and low-conductive particles are assumed to accompany the ﬂow, and conclusions are drawn for every numerical experiment. We found that high-conductivity suspended particles enhance heat transfer up to 2.5 times, while low-conductivity particles promote a much lower heat transfer enhancement. Relative heat transfer enhancement is more signiﬁcant at lower Re. The results indicate that suspended particles may be used either for heat transfer enhancement or by reducing pumping power at a ﬁxed heat transfer rate.